Implementation of scientific approach and teacher affective learning strategy of PAI in increasing student learning achievement - Zazinatul Basiroh (Prodi PGMI IAIN Salatiga, 2017)
This study aims to determine the application of scientific approach and affective learning strategy of Islamic education teachers in improving student achievement. This research used qualitative method, used observation, interview or document review. The data presented in verbal form was not in the form of numbers. Based on the results of research and discussion can be concluded the application of scientific approach by teachers Islamic education in Sekolah Dasar Negeri Plumutan and Madrasah Ibtidaiyah Darussalam Bancak was observing, asking, exploring, associate and communicate. Affective learning strategies in public primary Sekolah Dasar Negeri Plumutan and Madrasah Ibtidaiyah Darussalam Bancak done in two ways, the pattern of habituation and modeling or modeling. Implementation of scientific approach and affective learning strategy of learning Islamic education strongly support the success in improving student achievement. The result of this research showed that effectively and efficiently in accordance with the stages of learning with scientific approach and affective learning, then the purpose of learning can be achieved.